2020
DOI: 10.3390/su12187595
|View full text |Cite
|
Sign up to set email alerts
|

Perception, Motivation, and Satisfaction of Female Tourists with Their Visit to the City of Cordoba (Spain)

Abstract: The cultural and historical heritage of a city is a major resource for attracting tourists. Therefore, determining how to perceive and identify the characteristics of persons visiting a locality attracted by its heritage is relevant for the purpose of better meeting their expectations and needs. This research focuses on understanding the perceptions, motivations, and satisfaction of women visiting Cordoba (Spain). Thus, on the basis of a questionnaire completed by women visiting Cordoba between the months of J… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 81 publications
0
2
0
Order By: Relevance
“…On the other side, a higher number of research studies concluded that the amount of income significantly influences the choice of a tourist destination. (Kattiyapornpong, 2009;Anson et al, 2018;Escobar et al, 2020).…”
Section: The Discussion Of the Research Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…On the other side, a higher number of research studies concluded that the amount of income significantly influences the choice of a tourist destination. (Kattiyapornpong, 2009;Anson et al, 2018;Escobar et al, 2020).…”
Section: The Discussion Of the Research Resultsmentioning
confidence: 99%
“…In addition, it is observed that level of income has an influence on planning tourist trips since the groups with higher incomes are prone to planning short trips within domestic tourist destinations, in comparison to groups of tourists with lower incomes (Kattiyapornpong, 2009). There are conclusions that tourists that visit Córdoba have medium to high purchase power (Escobar et al, 2020). It is possible, in literature, to find studies which results show that amount of income does not influence the greater desire for traveling (Aziz et al, 2018).…”
Section: Literature Reviewmentioning
confidence: 99%